(untitled) (Journal of the College of Basic Education, 2023)
A friend gave me the book Anthology of Arab Poetry by Ibn al-Shajari, who died in the year 542 AH.As usual, I hastened to browse it first and read it carefully secondly, and the book Al-Mukhtarat Ibn Al-Shajari.It is precious because it contains rare and beautiful poems by pre-Islamic and Islamic poets with a large number ofUseful explanations and comments. After reading the texts, I found myself drawn to the poet’s poem.Qanab bin Umm Sahib, due to its preciousness and quality, a research project was born in my mind that revolves around thisIn the beginning, I thought that I would find other news and poems of the poet, but my attemptsIt failed, and I did not find any poetry by him except this poem, in addition to the scarcity of news about him.His life was Qa’nab bin Umm Sahib, Muqll, and Mghmur.Thus, I focused my attention on this unique poem, and I divided the research into an introduction.And three researches.